Hubungan Game Addiction dengan Risiko Attention Deficit Hyperactivity Disorder (ADHD) pada Anak Usia Sekolah - Zubaidah, Zubaidah; Arsila, Idha (Master of Nursing, Faculty of Medicine, Universitas Diponegoro, Indonesia, 2025)
The development of technology shows an increase the use of online devices including games. Games are fun for various age groups, including children. Game addiction causes psychosocial and mental problems that lead to the risk of Attention Deficit Hyperactivity Disorder (ADHD). Most previous studies have primarily focused on the prevalence of game addiction or its general impact on children's mental health, without directly examining the potential link between the level of game addiction and symptoms or risk of ADHD in school age children. The purpose of this study was to determine the relationship between game addiction and the risk of ADHD in school-age children in Ambal District, Kebumen Regency. This research was a descriptive study with survey approach. Data collection was conducted in February 2023 using probability sampling technique, called simple random sampling. The basis calculation uses Slovin formula until minimum number of respondents was obtained 128 repondents. Random sample selection uses RANDBETWEEN function in Microsoft Excel. Total sample was 128 pairs of parents and children in grades 4, 5, and 6 as respondents. The questionnaires were Indonesian Online Game Questionnaire (IOGQ) completed by the children and Indonesia of Assessment for Hyperactive Children's Behavior in Indonesia Scale completed by parents. Data were analyzed using Somers’d correlation test. The results showed that the highest percentage of game addiction in mild addiction category (65.6%) with 36.7% children not at-risk ADHD and 28.9% children at risk ADHD. Correlation results obtained p-value 0.000<0.05 and r = 0.448 which indicates the significant relationship between game addiction and the risk of ADHD with fairly strong relationship strength. The conclusion from this research is fairly strong, significant, and positive relationship between game addiction and the risk of ADHD in school-age children. Based on the results, the researchers suggest that necessary to supervise and monitor children from playing mobile devices, especially playing games. The next research is expected to involve a larger number of respondents, more effective methods, and other factors that have not been explored before.